Effect of Ultrasound Treatment in the Mass Transfer and Physical Properties of Salted Duck Eggs - Dang, Khoa Luu Mai; Le, Tuan Quoc; Songsermpong, Sirichai (Agriculture and Natural Resources, 2014)
The acceleration of the traditional process (TP) of salting duck eggs was studied using an ultrasound technique (60 kHz and 140 W) under three different process conditions—UPC1 (running time of 240 min), UPC2 (running time of 480 min), and UPC3 (running time of 720 min) during 48 hr. The ultrasound processes (UP) were compared with the imitated TP for changes in the water and salt contents, salt diffusion, the hardening ratio of egg yolk (HR) and the color of the egg yolk during pickling. It appeared that the rate of salt content in both the egg white and egg yolk was significantly increased while the rate of water content was significantly decreased when compared to the TP during pickling. The rates of L*, a* and b* color changes under the UP were more extended than those of TP during pickling. The HR was not changed during the first 36 hr for the TP while it was significantly increased for UP. An increased duration of ultrasonication led to an increased effective diffusivity of NaCl through the eggshell during salting, which was much greater than that of the TP. Among the three UP conditions, UPC3 after 48 hr provided an HR approximately equal to the TP after 288 hr and the diffusivity coefficient of NaCl was about 45–46 fold compared to the TP over the same period. In this study, the running time of the UP conditions seemed to be the major factor in accelerating the process of salting duck eggs.